Pendampingan Literasi Menulis Buku Anak di Sekolah Melalui Literacy Fair - Bayu Dwi Nurwicaksono; Suratni Suratni; Diah Amelia (Medan Resource Center, 2022)
The aim of this program is to foster the School Literacy Movement which is held independently by schools through The Literacy Fair. The method used is a participatory approach involving foster parents (teachers), students, and student guardians. The stages include (1) pre-production which includes assisting foster parents as facilitators and assisting children as subjects of children's book manuscript writers, (2) production which includes assisting in determining creative ideas, assisting in drafting essays, assisting in writing children's book manuscripts, assisting in manuscript revision children's books, assistance with layout layout for children's books, assistance with designing children's book covers, and assistance with trial printing of children's books, (3) post-production which includes assistance with ISBN registration for children's books and assistance with the final printing of children's books. As a result, this five-month literacy training succeeded in publishing seven books with ISBNs including one collection of works by children in playgroups and kindergartens, one collection of works by 1st grade elementary school children, one collection of works by 2nd grade elementary school children, one collection of works by 3th grade elementary school children, one collection of works by 4th grade elementary school children, one collection of works by 5th grade elementary school children, and one collection of works by 6th grade elementary school children. Recommendations for the implementation of this kind of literacy assistance program need to be carried out for six months so that the timeline is not too busy. In addition, the choice of words and the length of sentences in children's books must be adjusted according to the level. In terms of involving students, it needs to be done in layers, namely final year students (III) and intermediate level students (II) to create collaboration and realize regeneration.